2018
DOI: 10.3390/mi9080403
|View full text |Cite
|
Sign up to set email alerts
|

From Lab on a Chip to Point of Care Devices: The Role of Open Source Microcontrollers

Abstract: Microcontrollers are programmable, integrated circuit chips. In the last two decades, their applications to industrial instruments, vehicles, and household appliances have reached the extent that microcontrollers are now the number-one selling electronic chip of all kinds. Simultaneously, the field of lab-on-a-chip research and technology has seen major technological leaps towards sample handling, sample preparation, and sensing for use in molecular diagnostic devices. Yet, the transformation from a laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 34 publications
0
44
0
1
Order By: Relevance
“…These efforts supplement a wide range of existing open hardware and off-patent, generic biotechnologies which could play a role in expanding molecular testing capabilities [7,[113][114][115][116].…”
Section: Fosh Approaches In Covid-19 Diagnosticsmentioning
confidence: 99%
“…These efforts supplement a wide range of existing open hardware and off-patent, generic biotechnologies which could play a role in expanding molecular testing capabilities [7,[113][114][115][116].…”
Section: Fosh Approaches In Covid-19 Diagnosticsmentioning
confidence: 99%
“…In this scenario, a point-of-care (PoC) device (i.e., a rapid, robust, and cost-efficient device that can be used onsite and in the field, and which does not necessarily require a trained technician to operate [21]) is crucial and urgently needed for the detection of COVID-19. Figure 2 shows the dramatic impact of early detection of infectious diseases in controlling an outbreak [22][23][24].…”
Section: The Need For a Rapid Detection Methods And Portable Detectionmentioning
confidence: 99%
“…Recently, it was reported that the Diamond Princess cruise ship has been quarantined in Yokohama, Japan, due to a serious spreading of COVID-19 on this cruise, with at least 454 infected cases out of 3,700 passengers and crew (reported by WHO [7], 17 February 2020). The detection of COVID-19 may not have been prompt enough as they did not have enough test kits to diagnose all the passengers on the ship in order to timely respond to the rapid spreading of the disease [21]. [11]).…”
Section: Introductionmentioning
confidence: 99%
“…POCT also is designed for patients who have not been specifically trained to get self-test at home. The POCT equipment should be portable so that doctors and patients could use it anywhere [1][2][3][4][5]. The advantages of POCT could help doctors to continuously monitor the health state of patients, which is necessary for some chronic diseases such as cancers, diabetes, and heart diseases.…”
Section: Introductionmentioning
confidence: 99%